What is the best treatment forGiardia?. Issue 6 (June 2017) - Hess, Elizabeth; McMillion, Brent; Niere, Joanne
Abstract : EVIDENCE‐BASED ANSWER : The 5‐nitroimidazole (5‐NI) class of antimicrobials, including metronidazole and tinidazole, are 10% to 30% more likely to result in cure than other antiparasitic agents for Giardia in adults and children (SOR: A, meta‐analysis of RCTs). Single‐dose tinidazole is 40% to 90% more likely to result in cure than albendazole for eradication of Giardia in children (SOR: A, meta‐analysis of RCTs).